Yield and quality response of hydroponically grown tomatoes (Lycopersicon esculentum Mill.) to nitrogen source and growth medium - Langenhoven, Petrus (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--Stellenbosch University, 2004.